Segment Profitability and the Proprietary and Agency Costs of Disclosure - Berger, Philip G.; Hann, Rebecca N. (The Accounting Review, 2007)
We exploit the change in U.S. segment reporting rules (from SFAS No. 14 to SFAS No. 131) to examine two motives for managers to conceal segment profits: proprietary costs and agency costs. Managers face proprietary costs of segment disclosure if the revelation of a segment that earns high abnormal profits attracts more competition and, hence, reduces the abnormal profits. Managers face agency costs of segment disclosure if the revelation of a segment that earns low abnormal profits reveals unresolved agency problems and, hence, leads to heightened external monitoring. By comparing a hand-collected sample of restated SFAS No. 131 segments with historical SFAS No. 14 segments, we examine at the segment level whether managers' disclosure decisions are influenced by their proprietary and agency cost motives to conceal segment profits. Specifically, we test two hypotheses: (1) when the proprietary cost motive dominates, managers tend to withhold the segments with relatively high abnormal profits (hereafter, the proprietary cost motive hypothesis), and (2) when the agency cost motive dominates, managers tend to withhold the segments with relatively low abnormal profits (hereafter, the agency cost motive hypothesis). Our results are consistent with the agency cost motive hypothesis, whereas we find mixed evidence with regard to the proprietary cost motive hypothesis.